Extraction of Bioactive Compounds from Prestonia mollis Leaves and Their Impregnation into Polylactic Acid Using High-Pressure Technologies: Potential for Biomedical Application - Gabriel Alfonso Burgos-Briones; Lidia Verano-Naranjo; Cristina Cejudo-Bastante; Alex Alberto Dueñas-Rivadeneira; Casimiro Mantell-Serrano; Lourdes Casas-Cardoso (MDPI AG, 2023)
Enhanced solvent extraction (ESE) and pressurized liquid extraction (PLE) have been used for the first time to obtain antioxidant compounds from Prestonia mollis leaves. The effects of pressure (100-250 bar), temperature (55-75 °C) and the composition of the extraction solvent (ethanol, water and hydroalcoholic mixtures) were evaluated according to multilevel factorial designs. PLE provided the largest extraction yields compared to ESE, as well as a greater impact of the operating conditions studied. The highest total phenolic content was obtained when using a hydroalcoholic mixture (CO2/ethanol/water 50/25/25) through ESE at 100 bar and 75 °C. The antioxidant capacity of this extract is related to higher concentration levels of the identified flavonoids: Quercetin 3-O-xylosyl-rutinoside, Kaempferol 3-(2G-apiosylrobinobioside) and Kaempferol 4'-glucoside 7-rhamnoside. This extract was tested for the supercritical impregnation of polylactic acid (PLA), which is a polymer widely used in the biomedical industry. The influence of pressure (100-400 bar), temperature (35-55 °C), amount of extract (3-6 mL) and impregnation time (1-2 h) have been evaluated. The best results were obtained by impregnating 3 mL of extract at 100 bar and 55 °C for 2 h, achieving 10% inhibition with DPPH methods. The extract presented a potentially suitable impregnation of PLA for biomedical applications.